Artificial intelligence discrimination: how to deal with it? - Niemiec, William; Borges, Rafael F.; Barone, Dante A. C. (Anais do Workshop sobre as Implicações da Computação na Sociedade (WICS); 2022: Anais do III Workshop sobre as Implicações da Computação na Sociedade, 2022)
The emergence of artificial intelligence has brought many benefits to society through the automation of activities such as driving cars, product delivery, item classification, and predicting trends with a greater degree of accuracy. However, depending on how it is used, it may reflect persistent problems in society, such as discrimination. In this paper, we discuss discrimination by artificial intelligence. We begin by describing this problem and showing that it is a recurring and current problem. Then, we show the origin of this problem and propose a strategy to deal with it in order to prevent it from happening again. Lastly, we discuss future works and how the proposed strategy can be put into practice.